Pengaruh Budaya Organisasi, Tim Kerja dan Motivasi Intrinsik terhadap Komitmen Normatif Guru Sekolah Dasar Negeri di Batang Kuis - Damanik, Rapika Kesatriani; Sidauruk, Selna Aprilia; G.A.N, Septiana; Tarigan, M.Hilmi Irawan (JURNAL DIVERSITA, 2018)
This study aimed to determine (1) the effect of organizational culture to intrinsic motivation, (2) the effect of work team to intrinsic motivation, (3) the effect of organizational culture to normative commitment, (4) the effect of work team to normative commitment (5) the effect of intrinsic motivation to normative commitment and (6) the undirect effect who organizational culture and work team to normative commitment weather intrinsic motivation. The result showed that: (1) There is a significant direct possitive of effect between organizational culture and work team, individually to intrinsic motivation with significance level of 0,399 and 0,414. (2) There is a significant direct possitive of effect between organizational culture, work team and intrinsic motivation, individually to normative commitment with significance level of 0,324, 0,181 and 0,169. (3) There is a indirect effect between organizational culture and work team, individually to normative commitment with the significance level of 0,210 and 0,229 weather intrinsic motivation. The study concluded: (1) Organizational culture and work team has a direct effect, individually to intrinsic motivation by 16% and 17%. (2) Organizational culture, work team and intrinsic motivation, individually has a direct effect to normative commitment by 10%, 3,3% and 2,8%. Thus suggested to improve the normative commitment should be increased organizational culture, work team and intrinsic motivation of teacher.